2004
DOI: 10.1074/jbc.m310866200
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Citrate Transport Protein

Abstract: The mitochondrial citrate transport protein (CTP) has been investigated by mutating 28 consecutive residues within transmembrane domain III (TMDIII), one at a time, to cysteine. A cysteine-less CTP that retains wildtype functional properties, served as the starting template. The single Cys CTP mutants were abundantly expressed in Escherichia coli, isolated, and functionally reconstituted in a liposomal system. The accessibility of each single Cys mutant to two methanethiosulfonate reagents was evaluated by det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
(63 reference statements)
2
22
0
Order By: Relevance
“…Previous studies have shown that anomalous results of cysteine-specific chemical modification studies are often observed when the modified cysteine is located at the end of TM helices near the membrane/aqueous compartment interface (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that anomalous results of cysteine-specific chemical modification studies are often observed when the modified cysteine is located at the end of TM helices near the membrane/aqueous compartment interface (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Construction, Overexpression, and Isolation of Single-Cys CTP Variants-Single-Cys CTP variants were prepared as previously described (14). Briefly, single-Cys CTP genes were constructed using the QuikChange site-directed mutagenesis kit (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…With this background in mind, the current studies focused on characterizing the kinetic properties of a panel of singleCys mutants that we had previously constructed based on their predicted importance in the CTP mechanism (11,14,18). We identified ten mutations that display both substantially elevated K m values and reduced V max values, nine of which localize to two topographically distinct clusters within the CTP structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation, Expression, and Isolation of Single-Cys CTP Mutants-The nine single-Cys CTP-binding site mutants were constructed using the QuikChange site-directed mutagenesis kit and cloned into storage (NovaBlue) and expression (BL21(DE3)) hosts as described previously (20,23). Expression was induced with 1 mM isopropyl 1-thio-␤-D-galactopyranoside.…”
Section: Methodsmentioning
confidence: 99%